2010
DOI: 10.1007/s11423-010-9178-x
|View full text |Cite
|
Sign up to set email alerts
|

Representational guidance and student engagement: examining designs for collaboration in online synchronous environments

Abstract: In this paper we report the results of a study which investigated the affordances of multi-user virtual environments (MUVEs) for collaborative learning from a design perspective. Utilizing a mixed methods approach, we conducted a comparative study of the effect of varying representational and interactional design features on a collaborative design activity in three online synchronous environments. We compared environments featuring multiple modes of interaction (MUVEs), shared representations (text chat and 2D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In an evaluation of three online synchronous multiuser environments, greater learning seemed to occur in the situation where students used text chat and two‐dimensional still images rather than multiple modes of interaction (MUVEs or Multiple User Virtual Environments) and text‐only situations that rely solely on reading (Sullivan et al., ). Perhaps not surprisingly, students had more fun in the MUVEs but the simpler approach to interaction (text and two‐dimensional images) addressed the needs of student learning styles, whereas the MUVEs appealed to kinesthetic learners (a smaller percentage of students).…”
Section: Techniques For Student Engagement Onlinementioning
confidence: 99%
“…In an evaluation of three online synchronous multiuser environments, greater learning seemed to occur in the situation where students used text chat and two‐dimensional still images rather than multiple modes of interaction (MUVEs or Multiple User Virtual Environments) and text‐only situations that rely solely on reading (Sullivan et al., ). Perhaps not surprisingly, students had more fun in the MUVEs but the simpler approach to interaction (text and two‐dimensional images) addressed the needs of student learning styles, whereas the MUVEs appealed to kinesthetic learners (a smaller percentage of students).…”
Section: Techniques For Student Engagement Onlinementioning
confidence: 99%
“…Online collaborative learning requires the implementation of intercultural online learning using seamless and effective strategies, common interactive learning activities that embrace cultural diversity (Yang et al, 2014 ; Kumi-Yeboah et al, 2017 ). Such environments perform representative and interactive design functions for collaboration; create a sense of community and collaboration (Sullivan et al, 2011 ). Synchronous and asynchronous online environments act as the design of multi-user virtual environments for collaborative learning.…”
Section: Introductionmentioning
confidence: 99%
“…Provision of transportation costs and laboratory experiments. (Prasolova-Førland, 2008;Omale, et al 2009;De Lucia, et al 2009;El-Sabagh, 2011;Sullivan, et al 2011;Cheng & Wang 2011). Many studies have confirmed the effectiveness of employing the 3D digital environment in education, including A study by Bedeer (2014) that concluded the effectiveness of using virtual reality technology in developing cognitive achievement, visual thinking, and attitudes towards science among middle school students.…”
Section: Introductionmentioning
confidence: 99%